2018
DOI: 10.1016/j.cmet.2018.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Supercomplexes Do Not Enhance Catalysis by Quinone Channeling

Abstract: SummaryMitochondrial respiratory supercomplexes, comprising complexes I, III, and IV, are the minimal functional units of the electron transport chain. Assembling the individual complexes into supercomplexes may stabilize them, provide greater spatiotemporal control of respiration, or, controversially, confer kinetic advantages through the sequestration of local quinone and cytochrome c pools (substrate channeling). Here, we have incorporated an alternative quinol oxidase (AOX) into mammalian heart mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
93
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 54 publications
8
93
3
Order By: Relevance
“…Moreover, they indicate 458 that CI and CII can potentially outcompete for delivering electrons to AOX, a phenomenon that 459 is minimized by the presence of CIII. Our results with AOX expression substantially disagree 460 with those published by Fedor and Hirst (Fedor and Hirst, 2018). The reason for this discrepancy 461 is likely due to the unnoticed disruption of the supercomplexes under their experimental set up, 462…”
Section: Superassembly Of Oxphos Complexes Influences the Delivery Ofcontrasting
confidence: 52%
See 1 more Smart Citation
“…Moreover, they indicate 458 that CI and CII can potentially outcompete for delivering electrons to AOX, a phenomenon that 459 is minimized by the presence of CIII. Our results with AOX expression substantially disagree 460 with those published by Fedor and Hirst (Fedor and Hirst, 2018). The reason for this discrepancy 461 is likely due to the unnoticed disruption of the supercomplexes under their experimental set up, 462…”
Section: Superassembly Of Oxphos Complexes Influences the Delivery Ofcontrasting
confidence: 52%
“…The lack of stability of the respiratory supercomplexes upon disruption of mitochondrial 403 membranes raises serious concerns on the interpretation of recent experiments where recombinant 404 AOX was added to a preparation of sub-mitochondrial particles (Fedor and Hirst, 2018). The data 405 obtained suggested that the interaction of CI and CIII in supercomplexes does not modify the 406 delivery of electrons to the alternative oxidase AOX by CoQ.…”
Section: Superassembly Of Oxphos Complexes Influences the Delivery Ofmentioning
confidence: 99%
“…Complexes I, III and IV have been shown to exist in several higher order structures known as respiratory chain supercomplexes or respirasomes [1][2][3][4]. These structures have been suggested to reduce production of reactive oxygen species (ROS), improve complex stability and/or distribution throughout the protein dense environment of the IMM, and allow efficient channeling of substrates [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The isolation window was set at 1.2 m/z and precursors fragmented using stepped normalized collision energy of 28, 30 and 32. Resolution was at 35,000 resolution, AGC target at 2e5 and maximum IT time of 150 ms. Dynamic exclusion was set to be 30 seconds.…”
mentioning
confidence: 99%
“…Complex I further associates with respiratory complexes III and IV to form the respiratory supercomplex, the function of which is still under debate (Fedor and Hirst, 2018;Guo et al, 2017;Letts et al, 2016;Milenkovic et al, 2017). It has also been demonstrated that loss of complex III reduces the levels of/or impedes assembly of complex I, suggesting a dynamic interplay between the respiratory enzymes during their biogenesis (Acín-Pérez et al, 2004).…”
Section: Introductionmentioning
confidence: 99%